A Cytokine‐Delivering Polymer Is Effective in Reducing Tumor Burden in a Head and Neck Squamous Cell Carcinoma Murine Model. (13th May 2014) - Lin, Yuan; Luo, Jie; Zhu, Weichao Eric; Srivastava, Minu; Schaue, Dorthe; Elashoff, David A.; Dubinett, Steven M.; Sharma, Sherven; Wu, Benjamin; St. John, Maie A.
Abstract : Objective: This study aimed to evaluate the therapeutic efficacy of a novel polymer platform delivering cisplatin and cytokines in the treatment of head and neck squamous cell carcinoma (HNSCC). Study Design: In vivo study. Setting: Academic research laboratory. Subjects and Methods: Mice were randomized to receive implantation of (1) no polymer, (2) plain polymer, (3) plain polymer with local cisplatin injection, or (4) cisplatin polymer. The 2 groups of mice implanted with cisplatin polymer or no polymer were further randomized to receive (1) 4 Grays external beam radiation for 4 days or (2) no radiation. For cytokine studies, mice were grouped into (1) no polymer, (2) plain polymer, (3) plain polymer with intratumoral injection of recombinant CCL21 twice a week, (4) polymer containing parental dendritic cells, or (5) polymer containing dendritic cells secreting CCL21 (DC‐CCL21). Results: The cisplatin‐secreting polymer effectively reduced tumors in the mice by more than 16‐fold ( P <. 01). We also observed a statistically significant lower tumor weight among mice treated with cisplatin polymer and concomitant radiation compared to control groups. The DC‐CCL21 polymer reduced SCCVII/SF tumors in the C3H/HeJ mice by more than 41% ( P <. 01). Conclusion: Herein, we demonstrate the efficacy of a novel polymer platform in delivering cisplatin and cytokines. We also demonstrate that we can effectively grow dendritic cells in the polymer that can actively secrete CCL21 for a minimum of 5 days. This polymer may represent a new therapeutic modality for patients with HNSCC. Once this polymer platform is optimized, we will plan to pursue prospective trials in patients with HNSCC.